Kelimpahan dan Indeks Ekologis Perifiton di Sungai Bone Kabupaten Bone Bolango Gorontalo - Segita Kono; Ayinda Kristi Tiopo; Nuralim Pasisingi; Miftahul Khair Kadim (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Periphyton is an organism that lives attached to natural substrates such as rocks. The purpose of this study was to determine the abundance, abundance and ecological index of peryphyton in bone river bone bolango in gorontalo regency. This research was conducted in two stations, namely Panggulo Village, East Suwawa District and Tolomato Village, Suwawa Tengah District, Bone Bolango Regency. The results showed that in the Bone River there were 23 genera consisting of 8 classes. The highest relative abundance of periphyton was from the class Bacillariophyceaeby 33%. The periphyton diversity index at Station 1 ranges from 1,80 to 1,90 and at Station 2 ranges from 1,81 to 1,99. The periphyton uniformity index at Station 1 ranges from 0,70 to 0,75 and at Station 2 ranges from 0,86 to 0,93. The dominance index is almost no individual who dominates.